2006
DOI: 10.1007/s00204-006-0144-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined, multiple stressors on pyridostigmine-induced acute toxicity in rats

Abstract: A number of studies have evaluated the possibility that stress-induced changes in blood-brain barrier permeability enhanced the central effects of the carbamate acetylcholinesterase inhibitor, pyridostigmine. We previously found relatively little evidence of stress-induced changes in the acute toxicity of pyridostigmine in rats using a variety of restraint, forced running and forced swimming stress conditions. In this study, we evaluated the effects of sequential pre-exposure to multiple stressors on the acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Three studies in rodent models found that the adverse effects of PB were enhanced by stressors ( Abdel-Rahman, Abou-Donia, El-Masry, Shetty, & Abou-Donia, 2004 ; Abdel-Rahman, Shetty, & Abou-Donia, 2002 ; Friedman et al, 1996 ). Other studies showed reduced levels of acetylcholin-esterase (AChE) in the brains of animals given PB and exposed to stressors ( Baireddy, Mirajkar, Nallapaneni, Singleton, & Pope, 2007 ; Sinton, Fitch, Petty, & Haley, 2000 ). PB administered with the nerve agent sarin produced locomotor deficits ( Abou-Donia et al, 2002 ; Scremin et al, 2003 ), EEG abnormalities ( van Helden et al, 2004 ), changes in HRV ( Scremin et al, 2003 ) and increased markers of oxidative stress in urine ( Shih, Hulet, & McDonough, 2006 ).…”
Section: Animal Models Of Gwi Etiology and Pathologymentioning
confidence: 98%
“…Three studies in rodent models found that the adverse effects of PB were enhanced by stressors ( Abdel-Rahman, Abou-Donia, El-Masry, Shetty, & Abou-Donia, 2004 ; Abdel-Rahman, Shetty, & Abou-Donia, 2002 ; Friedman et al, 1996 ). Other studies showed reduced levels of acetylcholin-esterase (AChE) in the brains of animals given PB and exposed to stressors ( Baireddy, Mirajkar, Nallapaneni, Singleton, & Pope, 2007 ; Sinton, Fitch, Petty, & Haley, 2000 ). PB administered with the nerve agent sarin produced locomotor deficits ( Abou-Donia et al, 2002 ; Scremin et al, 2003 ), EEG abnormalities ( van Helden et al, 2004 ), changes in HRV ( Scremin et al, 2003 ) and increased markers of oxidative stress in urine ( Shih, Hulet, & McDonough, 2006 ).…”
Section: Animal Models Of Gwi Etiology and Pathologymentioning
confidence: 98%